Membentuk Pemahaman Sejarah Lewat Pendekatan Inkuiri pada Materi Perjuangan Kemerdekaan - Ningrum, Sulis Desiana; Agung, Achmad Imam; Buditjahjanto, I Gusti Putu Asto; Anifah, Lilik (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
This study aims to implement an inquiry-based learning model to improve students’ understanding and creativity in the History subject, specifically on the topic of the Struggle to Defend Indonesian Independence. The research was conducted as a classroom action research (CAR) involving students of class XI DKV 2 at SMK Negeri 6 Surabaya. The study consisted of three cycles, each comprising planning, action, observation, and reflection stages. Data were collected through observation sheets, learning achievement tests, and student response questionnaires. The results show that the inquiry-based learning model positively impacts both students’ understanding and creativity. The average test scores improved from 75.33 in the first cycle to 78.88 in the second and 85.75 in the third cycle. Students’ creativity also increased, as reflected in indicators such as initiative, ability to discuss, and ability to explain concepts in their own words. Questionnaire results indicated that 92.5% of students were interested, and 87.5% felt challenged by the inquiry-based learning process. In conclusion, the inquiry-based learning model is effective in enhancing students' understanding and active participation in learning history.